If S → BC, B → ε and C → d, then S → d. Select one: True or False.
![Question image](https://assets.quizgecko.com/question_images/lc8uflphzZNlWMIu16Ux7RR6jWBSmfTtrZ2MaCSd.jpg)
Understand the Problem
The question is asking whether the expression S → d can be derived from the given grammar rules. It presents a set of production rules and asks to infer the validity of a specific production.
Answer
True.
The final answer is True.
Answer for screen readers
The final answer is True.
More Information
The sequence of productions leads to the simplified form S → d, verifying the statement is true.
Tips
Ensure you correctly apply the epsilon production, which removes non-terminals when appropriate.
AI-generated content may contain errors. Please verify critical information